Systematic evaluation of the mechanisms of zoledronic acid based on network pharmacology. (December 2019) - Liang, Xue-Zhen; Li, Rui; Xu, Bo; Luo, Di; Liu, Guang-Bo; Peng, Jiang; Li, Gang
Highlights: The present study aimed to predict potential targets and screen identified targets of ZA using both computational reverse docking and chemical-protein interactome analysis, with additional assessment based on Gene Ontology (GO) and pathway analyses. Moreover, we constructed a compound-target-GO-pathway network to provide a systematic overview of potential and validated targets and mechanisms of action of ZA. Abstract: Zoledronic acid (ZA) is an FDA-approved drug and a third-generation bisphosphonate (BPs). A systematic evaluation of the mechanisms of ZA has not previously been performed. In this study, validated targets of ZA were screened using PubChem, Herbal Ingredients' Targets Database (HIT), Binding Database (BindingDB), and ChemBank, and potential targets of ZA were identified based on structural characteristics of ligands and proteins. The candidate targets were then assessed using GeneMANIA, Gene Ontology (GO), and pathway analysis, and molecule-target-GO-pathway networks were visualized using Cytoscape. Nine validated targets and 26 potential targets were obtained. The networks generated via this analysis showed that the candidate targets were associated with cell proliferation and metabolism as well as other biological processes (BP) and pathways. In general, ZA appeared to play crucial roles in multiple functions, including metabolism, regulation of vascular smooth muscle cell proliferation, and chemical carcinogenesis; a great deal of additional research must be performed. Moreover, the current study showed that it is feasible to analyze the mechanisms of ZA via target prediction, which facilitates systematic pharmacological evaluation.